THE ANALYSIS OF SUPPLY CHAIN RISK ON READY TO DRINK (RTD) PRODUCT USING HOUSE OF RISK METHOD - Silvya Ratri Nugraheni; Rahmi Yuniarti; Ratih Ardia Sari (Journal of Engineering and Management in Industrial System, 2017)
PT SGB is one of the companies that produce Ready To Drink (RTD) beverage as its product and its demand have increased every each year. The company’s supply chain process must be complex, it starts from materials order from supplier, materials storage management in warehouse, producting the beverage itself, finished good storing in the back-off factory then delivering to customers. All those processes belong to company’s supply chain stream and it is mapped as the element of Supply Chain Operation Reference (SCOR). From that complex processes, there were found supply chain risk as the problem. Risks that found in supply chain flow should be solved based on risk priority order. The method that used for analizing the risk is House of Risk (HOR), consist of two phases. The objective of the first phase of HOR is knowing the risk priority that should be mitigated based on the Aggregate Risk Potential (ARP) score, and the objective of the second phase of HOR are generating some preventive strategies and choosing the most effective strategy that suitable to be implemented in the company. Meanwhile, the Pareto chart is used to determine the choosen priority risk to be mitigated. There are 63 identified risk events based on SCOR elements, 43 identified risk agents, and 15 recommended preventive strategies according to the most effective sequence of strategies that applied in the company.